The mediating role of hope between perceived social support, basic psychological needs, and psychological adaptability in postpartum women with depression : a cross-sectional study - Zheng, Shiyu; Nor Mazlina, Ghazali; Voon, Siok Ping; Shen, Jilin (ASEAN Institute for Health Development (AIHD), Mahidol University, Thailand., 2025)
Postpartum depression (PPD) is a significant public health concern among women globally. This study examines the mediating role of hope in the relationship between perceived social support (PSS), basic psychological needs (BPNS), and psychological adjustment (PA) through a cross-sectional design. A minimum sample size of 403 was determined using Gpower. The study employed purposive sampling to recruit 501 participants from three hospitals in China, after excluding ineligible cases. The inclusion criteria required participants to have a Beck Depression Inventory score above 13, be at least 18 years old, possess a middle school diploma, be within 0 to 8 weeks postpartum, and have no postpartum illnesses or complications. The exclusion criteria included multiple deliveries. The instruments were the Psychological Adaptability Scale, Multidimensional Scale of Perceived Social Support, Basic Psychological Needs Scale,and Herth Hope Index,measuring PA, PSS, BPNS, and hope, respectively. Subsequently, three models were developed with BPNS and PSS as exogenous variables, hope as a mediator, and PA as the outcome. The findings revealed a significant positive correlation (p<0.01) among all variables in model 3. Hope partially mediated the connection between PSS and PA as well as between BPNS and PA. Moreover, alternative models 4 and 5 were created using BPNS, PSS, and PA as mediating variables to reinforce the credibility and validity of the model. Based on the Akaike Information Criterion (AIC) and Expected Cross-Validation Index (ECVI), model 3 was deemed the most statistically robust. These findings highlight the critical role of hope in enhancing PA among women with PPD. Healthcare providers and family members should focus on interventions that foster hope, alongside addressing social support and basic psychological needs, to improve psychological outcomes for women experiencing postpartum depression.